2005
DOI: 10.1897/04-305r.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the estrogenicity of Swiss midland rivers using a recombinant yeast bioassay and plasma vitellogenin concentrations in feral male brown trout

Abstract: In our study, we aim to characterize the estrogenicity of 18 independent rivers that receive effluent from sewage treatment works. During the winter and summer of 2003, we collected multiple water samples and measured environmental estrogens with an in vitro yeast-based reporter gene assay; estrogenicity was expressed as ng 17beta-estradiol equivalents (EEQ) per L of water. Estradiol equivalents values in winter ranged from 0.3 to 2.0 ng/L and, in summer, from 0.4 to 7.0 ng/L. Winter and summer EEQ values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
50
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 32 publications
6
50
1
1
Order By: Relevance
“…Both sampling points 6 and 4 do receive the effluent of the WWTP of Reckange (point 1), which could explain the slightly higher values measured for sampling points 4 and 6, compared to the other surface water samples at point 5, a distinct location in another catchment. These levels of estrogenic activity in surface waters in Luxembourg are somewhat higher than those obtained by Vethaak et al (2005) in the Netherlands (LOD -0.61 pmol EEQ l -1 ) or Vermeirssen et al (2005) in Swiss midland rivers (0.3-7 ng l -1 E2 equiv.). Studies in Belgium (Witters et al, 2001; and in UK (Jobling et al, 2009) indicate estrogenic activity in surface waters, which is of similar magnitude as presented in this study.…”
Section: Results From Yes Assay and Chemical Analysiscontrasting
confidence: 61%
See 1 more Smart Citation
“…Both sampling points 6 and 4 do receive the effluent of the WWTP of Reckange (point 1), which could explain the slightly higher values measured for sampling points 4 and 6, compared to the other surface water samples at point 5, a distinct location in another catchment. These levels of estrogenic activity in surface waters in Luxembourg are somewhat higher than those obtained by Vethaak et al (2005) in the Netherlands (LOD -0.61 pmol EEQ l -1 ) or Vermeirssen et al (2005) in Swiss midland rivers (0.3-7 ng l -1 E2 equiv.). Studies in Belgium (Witters et al, 2001; and in UK (Jobling et al, 2009) indicate estrogenic activity in surface waters, which is of similar magnitude as presented in this study.…”
Section: Results From Yes Assay and Chemical Analysiscontrasting
confidence: 61%
“…Studies in Belgium (Witters et al, 2001; and in UK (Jobling et al, 2009) indicate estrogenic activity in surface waters, which is of similar magnitude as presented in this study. The measured estrogenic activity could contribute to reproductive disturbances of natural populations of fish as suggested by Vermeirssen et al (2005) who demonstrated increased vitellogenin levels in feral male brown trout. Jobling et al (2005) pointed to medium to high risk for occurrence of intersex in wild roach when estrogenic activity was 1-10 or > 10 ng l -1 E2 equivalents, respectively.…”
Section: Results From Yes Assay and Chemical Analysismentioning
confidence: 91%
“…Rivers [17] Multiple independent yet similar locations were repeatedly sampled up and downstream from effluent discharges (Fig. 1).…”
Section: Study I: Variability Of Estrogenic Activity In Many Independentmentioning
confidence: 99%
“…It was concluded that possibly environmental conditions, but also method issues, contributed to the variability; particularly as the evaluation of the YES is not straightforward. [17,19] With the aim to produce a more robust data set, a second sampling campaign was conducted and 17 locations were sampled again in summer. This time, the three samples were collected with an exact two-week interval (± 3 h).…”
Section: Study I: Variability Of Estrogenic Activity In Many Independentmentioning
confidence: 99%
“…The development of rapid response methods using simple equipment has also become an attractive alternative to conventional chemical analytical techniques [16]. Among bioassays that have been considered, the yeast assay was successfully applied to determine activities in chemical and/or environmental samples [17]. Although many EDCs can survive drinking water treatment, little is known about the fate of RXR activity in drinking water [18].…”
mentioning
confidence: 99%